Manajemen pembelajaran mata pelajaran produktif dalam rangka peningkatan relevansi kebutuhan industri pada SMK Negeri 2 Wonosari Gunungkidul program studi teknik otomotif - Ardi Mintono; Samidjo Samidjo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
The research is aimed to get an illustration about the learning management including (1) Planning, (2) Organizing, (3) Implementing, (4) Evaluation, (5) Identifying the obstacles faced, (6) Identifying the supporting power (7) knowing anything that has been done, is doing and will be done by school in order to improve the industrial need relevance in SMK N 2 Wonosari Automotive technology department, especially in industrial work practice. This research used a qualitative approach, the location of research was SMK Negeri 2 Wonosari as a school that has achieved in Gunungkidul Regency. The data collecting methods used in this research were observations, interview, and documentation. The source of data includes the headmaster, vice headmaster of curriculum, teacher, student, school committee, supervisor and automotive industry. The data analysis being used was qualitative analysis from Miles and Huberman. The result of this research shows that the illustration of learning management on automotive productive subject is not relevance with industrial need yet, is caused by the following reasons, they are: (1) composing the administration lesson is not considering the conten, planning the learning media is not fulfilled with the need of up date technology (2) organizing learning material is based on the structure of developed school curriculum program is not involving the industrial world (3) the implementation in learning is not the same with the qualification demanded by industrial world (4) in the learning evaluation, there are competences that have not been taught to the students before doing practices on industrial work (5) the obstacles faced in improving the industrial need relevance there is no industrial involvement in arranging the curriculum (6) supporting powers that is owned by school can not be used in the appropriate lab work implementation (7) the efforts that has been done, is doing and will be done by school to increase the relevance of learning to industrial need are (a) the effort has been done: being responsive toward the evaluation of industrial work practice (b) the effort is doing capturing information from industrial world (e) the effort that will be done that is inviting automotive industries to involve in composing the curriculum in school.